Urinary Neutrophil Gelatinase-Associated Lipocalin Level is Associated with the Incidence of Postoperative Acute Kidney Injury: An Observational Study - Pontisomaya Parami; Tjokorda Gde Agung Senapathi; Gede Wirya Kusuma Duarsa; Nyoman Wande; Elysanti Dwi Martadiani; Syafri Kamsul Arif; Steven Okta Chandra; Samuel Dwiputra Widjanarko (Bali Journal of Anesthesiology)
Background: Acute kidney injury (AKI) remains a significant postoperative complication, often leading to increased morbidity and mortality. Traditional markers, such as serum creatinine, have limitations in early detection. Neutrophil gelatinase-associated lipocalin (NGAL) has emerged as a promising early biomarker for AKI. This study investigates the association between urinary NGAL and AKI incidence in postoperative patients admitted to the intensive care unit (ICU). Materials and Methods: This observational study included 89 postoperative ICU patients. Urinary NGAL was measured 24–48 h after surgery using an enzyme-linked immunosorbent assay kit. AKI was defined based on the Kidney Disease Improving Global Outcomes criteria. The predictive performance of urinary NGAL was compared with the postoperative-to-preoperative serum creatinine ratio. Results: Postoperative AKI occurred in 15.7% of patients. Urinary NGAL was significantly higher in AKI patients (43.87 vs. 2.87 µg/dL, P = 0.012). Regression analysis identified urinary NGAL levels (OR = 1.04, 95% CI = 1.01–1.06, P = 0.007) and serum creatinine ratio (OR = 40.5, 95% CI = 3.46–473.96, P = 0.003) as significant AKI predictors. The area under the curve for urinary NGAL levels was 0.71, compared to 0.75 for serum creatinine. Conclusion: Urinary NGAL is significantly associated with postoperative AKI and may serve as an early biomarker for renal injury. While serum creatinine demonstrated slightly better predictive performance, urinary NGAL offers earlier detection, potentially enabling timely intervention. Integrating urinary NGAL into perioperative monitoring may improve AKI risk stratification and patient outcomes.